Competitiveness: A systematic review of e-commerce and social media strategies for micro, small, and medium enterprises (MSMEs) - Irfan, Mohamad (Keynesia : International Journal of Economy and Business, 2025)
In the digital economy era, the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) is crucial for national economic resilience and growth. The adoption of digital technology, particularly e-commerce and social media, has become a critical factor in facing disruption and global competition. This research aims to synthesize empirical evidence from the last five years regarding strategies for enhancing MSME competitiveness through the adoption of e-commerce and social media. The study employs a Systematic Literature Review (SLR) method. Literature searches were conducted in indexed databases such as Google Scholar, ScienceDirect, Scopus, and Emerald Insight using the keywords "UMKM competitiveness", "e-commerce", "social media", "SMEs", and "digital transformation". A total of 28 relevant journals, published between 2019 and 2024, were selected through an inclusion and exclusion criteria process. The synthesis identifies four main strategies for enhancing competitiveness: Omnichannel Marketing Channel Integration Strategy, Digital Branding and Community Strategy, Innovation of Digital Platform-Based Business Models for value creation; and Digital Capability Improvement Strategy, which focuses on upgrading the skills of MSME human resources. Key enabling factors include government support, digital infrastructure, and easy access to digital payments. The main challenges faced are the digital skill gap, capital limitations, and cybersecurity. The integrated and strategic adoption of e-commerce and social media has proven significant in boosting MSME competitiveness. Successful implementation requires a holistic approach that focuses not only on technology but also on human resource development, innovative business models, and strong digital ecosystem support.